Durabilidade natural de estacas de sabiá (Mimosa Caesalpiniifolia Benth.) em campo de apodrecimento - Almeida, Gleiciana Nascimento de (Universidade Federal Rural do Semi-Árido, 2018)
The Mimosa caesalpiniifolia (Sabiá) is one of the main sources of cuttings and moirões production in the Brazilian Semi-arid, and can present a satisfactory and viable income for small and large rural producer. However, the factors that limit the use of wood for its purposes are related to its durability. Thus, the objective of the research was to evaluate the natural durability of sabiá stakes (Mimosa caesalpiniifolia Benth.) In a rotting field. In order to carry out the study, we used cuttings of Sabiá from different origins (Origin 1: native wood of a Caatinga area, Acopiara-CE; Origin 2: plantation wood, Upanema-RN, native wood of an area of Caatinga, Açu -RN) and for the purpose of comparison was adopted wood Pinus sp. In order to carry out the study, we used cuttings of Sabiá from different origins (Origin 1: native wood of a Caatinga area, Acopiara-CE; Origin 2: plantation wood, Upanema-RN, native wood of an area of Caatinga, Açu -RN) and for the purpose of comparison was adopted Pinus sp. purchased in local commerce, which were transformed into pieces with dimensions 2.0 x 2.0 x 30.0 cm. The experiment was carried out at the Federal Rural Semi-Arid University, Mossoró-RN Campus, from October to May 2018. The treatments were distributed in three randomized blocks, adjusting three replicates per block, totalizing nine specimens for each treatment. These samples were buried vertically up to half of their length (15 cm), with 25 cm sample spacing and between 1 m blocks. Monthly all specimens were removed for mass loss and deterioration index (by visual analysis), at the end of the experiment, the termites were identified. . In general, the provenances of sabiá presented a smaller loss of mass and less deterioration, in relation to pine wood and the termites identified were of the genus Heterotermas sp. Sabiá stakes proved to be resistant to the field test and no variation for resistance of the different provenances was detected.
Monografia
Keywords: Madeiras; Deterioração; Resistência natural; Xilófagos; Woods; Deterioration; Natural resistance; Xylophagous; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL